Efficacy and safety of traditional Chinese medicine external washing in the treatment of postoperative wound of diabetes complicated with anal fistula: Study protocol of a randomized, double-blind, placebo-controlled, multi-center clinical trial - Kang, Jian; Liu, Ya; Peng, Sihan; Tang, Xiao; Liu, Lu; Xie, Ziyan; He, Yuchi; Zhang, Xiyu (Frontiers in Pharmacology, 2022)
Introduction: Anal fistula is one of the commonest ailments seen by anorectal surgeons as surgery is currently the preferred treatment for it. Diabetes mellitus is a risk factor that can lead to slow wound healing after anal fistula surgery. Because of the large postoperative wound surface of anal fistula, patients with diabetes can have an increased probability of wound infection, which makes it hard to heal. There is an extensive clinical experience for wound healing in traditional Chinese medicine (TCM). The Jiedu Shengji decoction (JSD) is a widely used external washing decoction in clinical practice. However, the current evidence on it is still insufficient. Therefore, we report this carefully designed clinical trial to assess the efficacy and safety of JSD in the treatment of postoperative wounds in diabetic patients with anal fistula. Methods and analysis: This study was designed to be a randomized, double-blind, placebo-controlled, multi-center clinical trial. There were 60 eligible participants who were randomized at a 1:1 ratio to the intervention and placebo groups. Both groups received the same standard treatment. The intervention group was given external washing decoction of TCM (JSD), while the placebo group was given the placebo made of excipients and flavoring agents. The main outcome measures include wound healing, distribution of wound pathogens, levels of inflammatory mediators, and blood glucose. The secondary outcome measures included lipids, the quality of the life evaluation scale (Short-Form Health Survey 36). Assessments were performed before the start of the study, at 1st, 2nd, 3rd, and 4th weeks after the intervention, and at 8th, 12th, and 16th follow-up weeks. Discussion: The clinical study we proposed will be the first randomized, double-blind, placebo-controlled, multi-center clinical trial study to assess the efficacy and safety of TCM external washing (JSD) in the treatment of postoperative wounds in diabetic patients with anal fistula. Ethics and dissemination: The Medical Ethics Committee of Hospital of Chengdu University of Traditional Chinese Medicine has reviewed this study protocol and gave its approval and consent on 17 March, 2022 (Ethical Review Number: 2022KL-018).